Adequately Addressing Pediatric Obesity: Challenges Faced by Primary Care Providers. Issue 7 (July 2017) - Shreve, Marilou; Scott, Allison; Vowell Johnson, Kelly
Abstract : Objective: To assess the challenges primary care providers encounter when providing counseling for pediatric patients identified as obese. Methods: A survey assessed the current challenges and barriers to the screening and treatment of pediatric obesity for providers in northwest Arkansas who provide care to families. The survey consisted of 15 Likert scale questions and 4 open-ended questions. Results: Time, resources, comfort, and cultural issues were reported by providers as the biggest barriers in screening and the treatment of pediatric obesity. All providers reported lack of time as a barrier to providing the care needed for obese children. Cultural barriers of both the provider and client were identified as factors, which negatively affect the care and treatment of obese children. Conclusions: Primary care providers continue to experience challenges when addressing pediatric obesity. In this study, a lack of adequate time to address obesity was identified as the most significant current barrier and may likely be tied to physician resources. Although reimbursement for obesity is increasing, the level of reimbursement does not support the time or the resources needed to treat patients. Many providers reported their patients' cultural view of obesity influenced how they counsel their patients. Increasing providers' knowledge concerning differences in how weight is viewed or valued may assist them in the assessment and care of obese pediatric patients. The challenges identified in previous research continue to limit providers when addressing obesity. Although progress has been made regarding knowledge of guidelines, continuing effort is needed to tackle the remaining challenges. This will allow for earlier identification and intervention, resulting in improved outcomes in pediatric obesity. Abstract : Primary care providers often are the first healthcare professionals to identify pediatric patients who meet the diagnostic criteria of obesity. Historically, specific challenges that impede their ability to develop appropriate treatment plans for families of children who are obese have been identified by providers. A survey sent to primary care providers found that previous challenges such as time, reimbursement, and resources continue to be obstacles when addressing pediatric obesity. Cultural beliefs and both providers and families provide additional challenges to adequately address pediatric obesity.Supplemental digital content is available in the text.